(untitled) (Global Journal of Science Frontier Research, 2022)
The continuous growing worlds’ impact of climate change (global warming), including frequent natural disasters such as earthquakes, wildfires, etc.; rising food insecurity, infectious diseases, etc.; among others, causing economic, political, and civil unrest cannot be downplayed. Carbon dioxide (CO 2 ) is the most significant contributor to climate change, mainly generate through human-induced industrial and techno logical advancement activities. Africa is most vulnerable to the impact of climate change in the world. Hence, any effort to combat climate change in Africa will be an outstanding achievement towards mitigating the excessive effect of climate change globally. We proposed a surface response optimization method to optimize (mini mize) the CO 2 emissions in Africa. We utilized the desirability function approach to obtain the optimum value of the risk factors that minimize Africa’s CO 2 emissions. The minimum value of the CO 2 was obtained along with a 95% confidence region.